A Combined Experimental and First-Principle Calculation (DFT Study) for In Situ Polymer Inclusion Membrane-Assisted Growth of Metal-Organic Frameworks (MOFs). (5th June 2020) - Darvishi, Reza; Pakizeh, Esmaeil
Abstract : A simple yet effective strategy was developed to prepare a metal-organic framework- (MOF-) based asymmetric membrane by depositing the Zeolitic imidazolate framework-8 (Zif-8) layer on the aminosilane-functionalized surface of a polymer inclusion membrane via an in situ growth process. During the extraction of the ligand molecules from the source to stripping compartment, metal ions react with ligand, and layers of Zif-8 were gradually grown onto aminosilane-modified polymer inclusion membrane (PIM). The properties of the surface-grown Zif-8 nanocrystalline layer were well characterized by powder X-ray diffraction, adsorption-desorption analysis, and scanning electron microscopy. The potential use of these Zif-8-supported PIM membranes for the separation of gases N2, CH4, and CO2 was evaluated at two temperatures (25 and 50°C) and pressures (1, 3, and 5 bar), by comparing the permeability and selectivity behavior of these membranes with neat PIM. The gas permeability of both pure PIM (P CO 2 = 799.2   barrer ) and PIM-co-MOF (P CO 2 = 675.8   barrer ) increases with the temperature for all three gases, and the permeation rate order was CO2 > CH4 > N2 . The results showed that the presence of a layer of Zif-8 on the surface of the polymer inclusion membranes can get a slightly reduced permeability (~21%) but an enhanced selectivity of up to ~70% for CO2 /CH4 and ~34% for CO2 /N2 . In the case of both membrane types, the ideal permselectivity decreases with the temperature, but this decrease was slightly more pronounced for the case of PIM-co-MOF. To understand more details about the electronic structure and optical and adsorption properties of Zif-8 and M +Zif-8 (M = N 2, C H 4, and   C O 2 ) compounds, the periodic plane-wave density functional theory (DFT) calculations were used. The electronic band structures and density of states for pure Zif-8 showed that this compound is metallic. Also, using DFT, the formation energy of M +Zif-8 compounds was calculated, and we showed that the CO2 +Zif-8 composition is more stable than other compounds. This result suggests that the tendency of the Zif-8 compound to absorb the CO2 molecule is higher than that of other molecules. Confirming these results, DFT optical calculations showed that the affinity of the CO2 +Zif-8 composition to absorb infrared light was greater than that of the other compounds.